1978
DOI: 10.2136/sssaj1978.03615995004200040003x
|View full text |Cite
|
Sign up to set email alerts
|

Copper and Cadmium Adsorption Characteristics of Selected Acid and Calcareous Soils

Abstract: Samples of two New York soils, an acid and a neutral silt loam, were equilibrated with Cu2+ and Cd2+ solutions in concentrations ranging from 10−5 to 10−4M in distilled water and in 0.01M CaCl2. The extent of complexation and adsorption of the heavy metals was measured using specific ion electrodes and atomic absorption. The data were found to fit the Langmuir adsorption model, and the Cu2+ adsorption maxima were greater than those of Cd2+ for both soils. Acid soils demonstrated much less ability to retain the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1
7

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(64 citation statements)
references
References 0 publications
2
54
1
7
Order By: Relevance
“…Pode-se atribuir as maiores concentrações de zinco, nas camadas mais superficiais da turfa, as maiores porcentagens de matéria orgânica nestas camadas. Por outro lado, as pequenas variações das concentrações de cobre, em função da profundidade examinada, pode ser devida a maior afinidade deste elemento pela matéria orgânica 25 . A matéria orgânica de solos e sedimentos geralmente é oxidada com água oxigenada para determinação de micronutrientes 26 .…”
Section: Resultsunclassified
“…Pode-se atribuir as maiores concentrações de zinco, nas camadas mais superficiais da turfa, as maiores porcentagens de matéria orgânica nestas camadas. Por outro lado, as pequenas variações das concentrações de cobre, em função da profundidade examinada, pode ser devida a maior afinidade deste elemento pela matéria orgânica 25 . A matéria orgânica de solos e sedimentos geralmente é oxidada com água oxigenada para determinação de micronutrientes 26 .…”
Section: Resultsunclassified
“…When present in calcareous soils, it has been shown that increasing OM content (0.4 to 4.8%; within the range of our study) decreases the quantity of plant-available Cu (Ghasemi-Fasaei et al, 2006) due to Cu complexation with organic species. Between 80 and 100% of Cu added to neutral or calcareous soils has been shown to be organically complexed (Cavallaro and McBride, 1978;McBride and Blasiak, 1979).…”
Section: Alfalfa Et Growth and Alfalfa Cu Concentrationmentioning
confidence: 99%
“…When present in calcareous soils, it has been shown that increasing OM content decreases the quantity of plant-available Cu (Ghasemi-Fasaei et al, 2006) because of Cu complexation with organic species. Between 80% and 100% of Cu added to neutral or calcareous soils has been shown to be organically complexed (Cavallaro and McBride, 1978;McBride and Blasiak, 1979).…”
Section: Soil Science and Volume 175 Number 12 December 2010mentioning
confidence: 99%
“…In soils with pH values greater than 7.0, soluble Cu can react to form CuO, CuCO 3 , or mixed hydroxycarbonate mineral species (McBride and Bouldin, 1984;Ponizovsky et al, 2007), although most of the Cu is strongly adsorbed to soil organic matter (OM) in basic soils because of greater OM solubility and increasing pH-dependent charge associated with increasing soil pH (McBride and Blasiak, 1979). Cavallaro and McBride (1978) showed that more than 80% of Cu added to neutral pH soil was in complexed form, whereas McBride and Blasiak (1979) showed that 99.9% of total soluble Cu was complexed with organic phases at pH 8. McBride and Bouldin (1984) found evidence of malachite precipitation in a Cu-contaminated calcareous soil (~3%Y4% free carbonate), yet the soil contained 5.3% OM, and greater than 95.5% of the Cu in soil solution was complexed with organic species.…”
mentioning
confidence: 99%